IMPROVING STUDENTS’ MOTIVATION IN CASE OF TEAM-BASED LEARNING METHOD - M.V. Khaitovych; V.S Potaskalova; N.O. Savelieva-Kulyk; O.A. Temirova; I.M. Sytnyk (Медична наука України, 2019)
Relevance. The learning motivation of student is the main goal of the teacher. Perspective is introducing of active forms of teaching.